ANALISIS WACANA GENDER DALAM BUKU ANAK - Maya Lestari, - (2022)
The purpose of this study is to explore how masculinity and femininity are represented in children's books which are widely used in the process of early childhood education by both parents and teachers. We analyzed the texts/stories and illustrations of 38 children's books published between 2016-2020 by five well-known publishers in Indonesia. The results of the analysis show that these children's books preserve, negotiate, and challenge gender discourse that is widely circulated in society. As such, this urgency is the responsibility of teachers, parents and other adults, both at home and in the educational setting, with a view to providing children with high quality learning. To be able to achieve this, teachers, parents, and other adults of course need to be aware of gender representation issues and be able to critically reflect on the content in children's books and what messages are contained and conveyed in them both verbally and physically. directly or indirectly